Team-Based Learning Intervention to Improve Obesity Education in Medical School - Amber Olson; Rosanna Watowicz; Eileen Seeholzer; Katherine Lyons; W. Scott Butsch; Colleen Croniger (Association of American Medical Colleges, 2023)
Introduction Obesity is a multifactorial chronic disease and a major contributor to numerous health conditions. Despite the high prevalence, costs, and health effects of obesity, physicians are largely unprepared to treat it. Most medical students and residents lack sufficient training in obesity and obesity management. Methods We evaluated a two-part team-based learning seminar (TBL) on obesity pathogenesis and treatment for first-year medical students at Case Western Reserve University School of Medicine (CWRU SOM). A questionnaire on attitudes toward obesity and self-perceived knowledge of obesity was administered before and after the TBL, utilizing Likert scales. Results Of 183 medical students who attended both TBLs, 155 (85%) completed the baseline questionnaire, and 127 (69%) completed the postintervention questionnaire. Confidence in treating obesity increased significantly from preintervention (M = 2.7, SD = 1.0) to postintervention (M = 3.7, SD = 0.8). The attitude that obesity is caused by poor personal choices decreased significantly from preintervention (M = 2.8, SD = 0.9) to postintervention (M = 2.1, SD = 0.9). Self-perceived knowledge of obesity in all nine areas-epidemiology, energy homeostasis, etiologies, nutrition, physical activity, behavior, pharmacology, surgery, and language-increased significantly. Discussion Despite obesity being one of the most prevalent health concerns, obesity education in medical school is scant. This TBL resulted in improved attitudes toward obesity and self-perceived knowledge of obesity among first-year medical students at CWRU SOM and offers a practical mechanism to introduce more obesity education into undergraduate medical curricula.